Impact of abdominal compression on setup error and image matching during radical abdominal radiotherapy - Chu, K; Cooke, R; Van Den Heuvel, F; Mukherjee, S; Hawkins, M (Elsevier, 2019)
Purpose To determine the impact of abdominal compression (AC) on setup error and image matching time. Materials and methods This study included 72 liver, pancreas and abdominal node patients treated radically from 2016 to 2019 in a single centre. Patients received either SBRT or conventional radical fractionation (CRF). Compressed patients were supine, arms up with kneefix and AC equipment. Uncompressed patients were supine, arms up with kneefix. All patients received daily online-matched CBCTs before treatment. Initial setup error was determined for all patients. Registration error was assessed for 10 liver and 10 pancreas patients. Image matching times were determined using beam on times. Statistical tests conducted were an F-test to compare variances in setup error, Student’s t-tests for setup error and average image analysis, and a Wilcoxon Mann Whitney test for imaging matching time analysis. Results Initial setup displacement was similar between compressed and uncompressed patients. Displacements > 1 cm occurred more frequently in the longitudinal direction for most patients. SBRT patients required more additional manual positioning following imaging. Mean absolute registration error in the SI direction was 5.4 mm and 3.3 mm for uncompressed and compressed pancreas patients respectively and 1.7 mm and 0.8 mm for uncompressed and compressed liver patients respectively. Compressed patients required less time for image matching and fewer images per fraction on average. Repeat imaging occurred more frequently in SBRT and uncompressed patients. Conclusions Although abdominal compression has no significant impact on setup error, it can reduce imaging matching times resulting in improved treatment accuracy.